PENERAPAN METODE FERNANDEZ DALAM PERANCANGAN MODEL KNOWLEDGE MANAGEMENT SYSTEM PADA HALL OF ARMOR BEKASI - Herryansyah . (JURNAL GAUNG INFORMATIKA, 2020)
Hall of Armor Bekasi as an organization engaged in providing services such as armor costume-making for various events. To improve human resource capabilities in providing quality and quantity of product services to optimum level, Hall of Armor Bekasi requires better support in information and communication technologies to improving the ability of personnel. Knowledge Management is one of the efforts to manage the resources of knowledge possessed by every person on this organization. This study aims to produce a model of knowledge management system in accordance with the conditions of Hall of Armor Bekasi. Using Fernandez’s method, the Contingency Factor to determine the form of knowledge management process that is suitable for the organization, as well as through prototyping to create a model of webbased KMS. This study concluded that KMS has priority on knowledge sharing is verysuitable to be applied in the Hall of Armor Bekasi as adjusted by the daily condition of the organization. Which are all of this efforts, arranged in order to improve the quality of human resources in the Hall of Armor Bekasi, which will support the quality and quantity of products of this organization in the future.